Evaluating the clinical and cost-effectiveness of permissive hypotension in critically ill patients aged 65 years or over with vasodilatory hypotension: Statistical and health economic analysis plan for the 65 trial in article*. (August 2020) - Thomas, Karen; Patel, Akshay; Sadique, M Zia; Grieve, Richard D; Mason, Alexina J; Moler, Silvia; Gordon, Anthony C; Rowan, Kathryn M; Mouncey, Paul R; Lamontagne, Francois; Harrison, David A
The 65 trial is a pragmatic, multicentre, parallel-group, open-label, randomised clinical trial of permissive hypotension (targeting a mean arterial pressure target of 60–65 mmHg during vasopressor therapy) versus usual care in critically ill patients aged 65 years or over with vasodilatory hypotension. The trial will recruit 2600 patients from 65 United Kingdom adult general critical care units. The primary outcome is all-cause mortality at 90 days. An economic evaluation is embedded. This paper describes the proposed statistical and health economic analysis for the 65 trial.